Indonesian Undergraduate EFL Students' Perception of the Use of Debate as Learning English-speaking Method - Saputra, Eko Restu; Lumbanbatu, Ira Maria Fran (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Debating improves students' speaking abilities and fosters spontaneous critical thinking without the need for prior preparation. In the absence of recent research on the topic, the current study aims to explore the benefits and the challenges the English Department students experienced during the implementation of the debate in the learning English-speaking process. The participants of this study were English Department students of Universitas Negeri Malang who had taken the Speaking for Academic Purposes course. A mixed-method study was conducted, by employing an explanatory sequential design to answer the formulated research questions. The quantitative data were collected through an online questionnaire and were analyzed by using Microsoft Excel. Meanwhile, the qualitative data were obtained from the interview and were analyzed by employing the interactive model data analysis of Miles et al. The result showed that most students have positive responses to the use of debate in speaking class and debate could improve their speaking skill. The challenges they encountered during the implementation such as lack numbers of meeting and the duration, limited time for preparing debate, also difficulty in understanding the debate method caused the insignificant result of speaking skill enhancement. The debate system was varied, depending on the lecturers. The result may be used as reference for English teachers to utilize debate in English-speaking class. Likewise, the future researchers are suggested to conduct action research employing debate in English-speaking class.